Dependence of the fracture mode on the welding variables in the resistance spot welding of ferrite-martensite DP980 advanced high-strength steel - Pouranvari, Majid (Materiali in tehnologije, 2012)
Failure mode is a qualitative measure of the performance of a resistance spot weld. To ensure the reliability of resistance spot welds during a vehicle's lifetime, the process parameters should be adjusted so that the pull out failure mode is guaranteed. Dual-phase steel resistance spot welds are prone to interfacial failure mode. In this paper the effects of welding parameters, including the welding current, the welding time and the electrode force, on the failure mode of DP980 resistance spot welds are investigated. The process window to obtain the desired pullout failure mode was determined. It was shown that increasing the electrode force increases the minimum welding current and the welding time required to obtain the PF mode.
Keywords: uporovno točkovno varjenje; dupleksna jekla; prelom